Pengaruh Tingginya Uang Hantaran Perkawinan terhadap Penundaan Perkawinan di Desa Temerloh, Negeri Pahang Malaysia Perspektif Maqashid Syari'ah - Nur Maizaitul Azerah Binti Mohd Sayuti; Ibnu Radwan Siddik Turnip (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to examine the effect of high dowry money in marriage against the postponement of marriage in Temerloh Village, Pahang State Malaysia in the perspective of maqashid shari'ah. This research is an empirical legal research, with a sociological approach to law. Data sources were obtained through interviews with a number of respondents and observations, which were then analyzed qualitatively. The results showed that there are still many people in Temerloh Village who practice dowry money so high that it has an impact on delaying marriage in several families in the village. The high dowry money is based on education, occupation and social status of the woman to be married. In the perspective of maqashid shari'ah, the high practice of dowry money that causes delays in marriage for those who are less fortunate is not in accordance with the aspect of hifz al-din (maintaining religion), because Islamic sharia advocates simplicity and ease in matters of dowry and financing in a marriage. Moreover, the postponement of marriage caused by the high amount of marriage dowry money is feared to result in actions that are not in accordance with religious values.